Examining the asymmetric effects of third country exchange rate volatility on trade between the US and the EU - Chien-Hui Lee; Shu-Hui Li; Jen-Yu Lee (Journal of Risk and Financial Management, 2022)
This paper aims to examine the symmetric and asymmetric effects of third country exchange rate volatility on the trade flow between the US and EU from January 2003 through March 2021. The monthly disaggregated data of the top twelve export and import industries are the sample frame. We find that separating increased volatility from declines and introducing a nonlinear adjustment to the volatility shows a more significant outcome than symmetric analysis. Different industries carry distinctive behaviors regarding exchange rate risk, and the third country effect plays a vital role in trade. Moreover, increased CNY/USD real exchange rate volatility increases bilateral trade between the US and EU.
Keywords: 650; asymmetric effects; disaggregated data; exchange rate volatility; trade flows